Pelatihan Alat Peraga Kincir Angin Dalam Pembelajaran Matematika Siswa SD - Rospala Hanisah Yukti Sari (Pakis Journal Institute, 2024)
This activity is carried out in an effort to help teachers convey mathematical concepts and help students understand mathematical concepts. This activity was carried out at SD Negeri 2 Kereng Bangkirai Palangka Raya and MIS Fathul Iman Palangka Raya. The activity was carried out in 3 stages, namely: 1) Gathering with the school; 2) implementation of activities; and 3) handing over teaching aids to the school. The results of this activity are: 1) At SD Negeri Kereng Bangkirai, students can participate well. Most students understand the concepts conveyed using windmill props. Students also enjoy learning with teaching aids. This can be seen from the enthusiasm of the students when the windmill props are used by the students. 2) The activity at MIS Fathul Iman is that almost all Class 1 students can overcome their boredom with the availability of windmill tinsel. Apart from that, they also actively answer during the lesson.